Invertebrate Grazing on Live Turtlegrass (Thalassia testudinum): A Common Interaction That May Facilitate Fungal Growth - Boyd, Anjali D.; Walker, Nia S.; Valdez, Stephanie R.; Zhang, Y. Stacy; Altieri, Andrew H.; Gulis, Vladislav; Crain, Caitlin; Silliman, Brian (Frontiers in Marine Science, 2022)
In coastal wetlands and tropical reefs, snails can regulate foundation species by feeding on marsh grasses and hard corals. In many cases, their impacts are amplified because they facilitate microbial infection in grazer-induced wounds. Whether snails commonly graze live plants and facilitate microbial growth on plants in tropical seagrass systems is less explored. On a Belizean Caye, we examined patterns in snail-generated grazer scars on the abundant turtlegrass (Thalassia testudinum). Our initial survey showed the occurrence of snail-induced scarring on live turtlegrass blades was common, with 57% of live leaves scarred. Feeding trials demonstrated that two of five common snails (Tegula fasciata–smooth tegula and Smaragdia viridis–emerald nerite) grazed unepiphytized turtlegrass blades and that smooth tegula abundance had a positive relationship with scarring intensity. Subsequent surveys at three Caribbean sites (separated by >150 km) also showed a high occurrence of snail-induced scars on turtlegrass blades. Finally, simulated herbivory experiments and field observations of a turtlegrass bed in Florida, United States suggests that herbivore damage could facilitate fungal growth in live seagrass tissue through mechanical opening of tissue. Combined, these findings reveal that snail grazing on live turtlegrass blades in the Caribbean can be common. Based on these results, we hypothesize that small grazers could be exerting top-down control over turtlegrass growth directly via grazing and/or indirectly by facilitating microbial infection in live seagrass tissue. Further studies are needed to determine the generality and relative importance of direct and indirect effects of gastropod grazing on turtlegrass health.